A NEW READING OF CATULLUS 25.5 - R. K. R. Thornton; A. Elliot (Exemplaria Classica, 2016)
The fth line of Catullus’s poem 25 is a notorious crux. 74 emendations have been proposed since the fteenth century. Thornton and Elliot propose a new line to satisfy the demands of metre, sentence- structure, and coherence with the corpus; and give a closely argued case for how the amendment proposed derives from the scribe’s marks.